A STUDY OF INTELLECTUAL POTENTIAL OF A MICRO-BUSINESS - Mojseyenko, Iryna (Journal of European Economy, 2017)
The article presents approaches to analyzing the intellectual potential of entrepreneurial structures. The author proposes to carry out analysis of the intellectual potential of micro-business on the basis of fuzzy set techniques.